ANALISIS RASIO SOLVABILITAS DAN PENGARUHNYA TERHADAP RENTABILITAS PADA PT. KIMIA FARMA, TBK - Mangopo, Yuni Riskita (Yudishtira Journal : Indonesian Journal of Finance and Strategy Inside, 2024)
This study aims to determine the level of solvency ratio for four years starting from 2016-2019 and to find out whether there is a significant influence between the solvency ratio and rentability in PT. Kimia Farma, Tbk. PT. Kimia Farma, Tbk is one of the State-Owned Enterprises (SOEs) engaged in the pharmaceutical industry. The data used in this study is the company’s financial data in the form of financial position reports and profit/loss statements for four periods. The data analysis method used is the solvency ratio, the profitability ratio, and the comparison between the solvency ratio and the profitability ratio to find out if there is a significant influence between the two ratios. The results of this study show that the solvency ratio level from 2016-2019 is not good, this is because the results of the ratio calculation every year have increased. From the results of this study, it can also be seen that there is no significant influence between solvency ratio and profitability, this is because it is not debt that affects profitability but other factors such as operational costs and cost of goods sold